Mobile game based learning for males having sex with males peer educators in India - Roy, Anupama (2013)
This thesis aims to examine the effectiveness of a mobile phone based SMS game as a learning intervention for the Peer Educators of the Males having Sex with Males (MSM) groups in Kolkata, India. MSM groups are marginalised and are at higher risk of HIV/AIDS, falling under the core groups for the National AIDS Control and Prevention programmes in India. Peer to peer education for behaviour change in HIV/AIDS prevention projects is a bottom up approach to reach out to this marginalised population for HIV prevention. Training is in place for MSM peer educators but research shows gaps in their support and learning needs.